WHIRLY1 Functions in the Control of Responses to Nitrogen Deficiency But Not Aphid Infestation in Barley. Issue 3 (5th May 2015) - Comadira, Gloria; Rasool, Brwa; Kaprinska, Barbara; García, Belén Márquez; Morris, Jennifer; Verrall, Susan R.; Bayer, Micha; Hedley, Peter E.; Hancock, Robert D.; Foyer, Christine H.
Abstract : A protein that has a role in the control of photosynthetic gene expression and protection against low nitrogen-induced stress. Abstract: WHIRLY1 is largely targeted to plastids, where it is a major constituent of the nucleoids. To explore WHIRLY1 functions in barley ( Hordeum vulgare ), RNA interference-knockdown lines (W1-1, W1-7, and W1-9) that have very low levels of HvWHIRLY1 transcripts were characterized in plants grown under optimal and stress conditions. The WHIRLY1-1 (W1-1), W1-7, and W1-9 plants were phenotypically similar to the wild type but produced fewer tillers and seeds. Photosynthesis rates were similar in all lines, but W1-1, W1-7, and W1-9 leaves had significantly more chlorophyll and less sucrose than the wild type. Transcripts encoding specific subsets of chloroplast-localized proteins, such as ribosomal proteins, subunits of the RNA polymerase, and thylakoid nicotinamide adenine dinucleotide (reduced) and cytochrome b 6 / f complexes, were much more abundant in the W1-7 leaves than the wild type. Although susceptibility of aphid ( Myzus persicae ) infestation was similar in all lines, the WHIRLY1-deficient plants showed altered responses to nitrogen deficiency, maintaining higher photosynthetic CO2 assimilation rates than the wild type under limiting nitrogen. Although all lines showed globally similar low nitrogen-dependent changes in transcripts and metabolites, the increased abundance of FAR-RED IMPAIRED RESPONSE1-like transcripts in nitrogen-deficient W1-7 leaves infers that WHIRLY1 has a role in communication between plastid and nuclear genes encoding photosynthetic proteins during abiotic stress.